An introduction to systematic reviews - Gough, David; Oliver, Sandy; Thomas, James (London : Sage pub, 2017)
David Gough, Sandy Oliver, and James Thomas' "Introduction to Systematic Reviews" stands as a definitive guide for researchers seeking to master the intricacies of evidence synthesis. The book offers a clear and comprehensive roadmap, spanning from the foundational principles to the advanced techniques of systematic reviews. By deftly balancing theoretical underpinnings with practical applications, the authors create a valuable resource for both novice and experienced researchers. The book$1 (Bs structured approach, coupled with its emphasis on precision and accuracy, solidifies systematic reviews as a gold standard in evidence-based research. While the book excels in providing a broad overview, its accessibility and clarity make it an indispensable tool for anyone embarking on a systematic review journey.s
Includes bibliographical references (p. 298-322) and index.
Keywords: Social sciences - Research Methodology; Research Methodology; Research Design; Systematic reviews; Meta-ethnography.; Evidence-based practice